Biorefinery of microalgae – opportunities and constraints for different production scenarios. Issue 6 (19th May 2014) - Hariskos, Ioanna; Posten, Clemens
Abstract In order to design economically feasible production processes it is necessary, as part of the biorefinery concept, to valorize all constituents of the microalgal biomass. Such an approach requires appropriate biorefinery side‐process strategies to be adapted to production of the primary product. These strategies are particularly valid for microalgae, since the composition and amount of residual biomass can vary significantly depending on cell stoichiometry and cultivation techniques. This review investigates opportunities and constraints for biorefinery concepts in production scenarios for four different products from microalgae with different market volumes, including high‐ and medium‐value products, whole cells and biodiesel. Approaches to close material and energy balances, as well as to adapt the biorefinery according to biological potential, process routes, and market needs are presented, which will further contribute to making the biorefinery concept a success.